CONTROL OF METALLURGICAL PROCESSES IN THE PRODUCTION OF CASTINGS OF ALUMINUM-BASED ALLOYS, USING COMPUTER ANALYSIS DATA - D. S. Morozov; P. E. Lushchik; I. V. Shestyuk (Литьë и металлургия)
The mathematical models and results of classification of alloys on the basis of aluminum on the specified brand with use of parameters of the computer thermal analysis are presented.